PERAN ORANG TUA DALAM MENANAMKAN PENDIDIKAN IMAN ANAK PASCA SAKRAMEN BAPTIS DI STASI SANTA MARIA ASSUMPTA CARUBAN - Dina, Angelina; Sulistiyo, Robertus Joko (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
This study aims to analyze the extent of parents' awareness of their duties and responsibilities as the primary educators in their children's faith life after receiving the Sacrament of Baptism, as well as the challenges they face in fulfilling this role. This research employs a qualitative approach through interviews with 10 married couples who are members of the community at St. Maria Assumpta Church in Caruban. The findings indicate that parents play a crucial role in their children's faith education after receiving the Sacrament of Baptism. Parents who actively guide, set an example of Christian living, and engage in church activities have a significant impact on their children's faith development. However, several challenges arise, including parents' busy schedules, a lack of understanding of their religious responsibilities, and the influence of a social environment that does not always support Christian values. Therefore, support from the church community and the surrounding environment is essential to help parents fulfill their role optimally.